ADOLESCENT’S PEER AND FAMILY INFLUENCE IN SMOKING RELAPSE - Putu Indraswari Aryanti; Erva Elli Kristanti (EZRA SCIENCE BULLETIN, 2023)
Background: Psychologically, adolescents are still in the identity-seeking phase so they often follow or imitate the people around them in order to be accepted in their environment. It is necessary to identify the influence of peers and family on adolescent smoking relapse. Objective: To identify the influence of peers and family on the incidence of relapse of adolescent smoking. Method: Quantitative with cross-sectional design. The target population is teenage respondents aged 12-15 years in classes VII, VIII, and IX at SMP X Kediri. The inclusion criteria were adolescent smokers and those who had smoked. The sample size is 45 respondents and was selected by simple random. The independent variable is the incidence of smoking among peers and family members and the dependent variable is the incidence of smoking relapse in adolescents. The instruments used were peer and family smoking questionnaires. Analysis of the data used to analyze the relationship using the Spearman correlation test with α = 0.05. Results: Selected 46 respondents participated in this study. The results of statistical tests showed that smoking relapse behavior in adolescents was not related to family interpersonal relationships (p = 0.879) or peers (p = 0.379). Conclusion: There is a shift in values in a society where interpersonal relationships with peers and family are not predictors of smoking relapse in adolescents.